The Views of Sheikh Kholil Bangkalan on Moral Education - Yanti, Ili; Muchlis, Madian M. (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Moral education is very important besides learning to understand the subject matter. This study aims to describe the thoughts or views of Sheikh Kholil Bangkalan on moral education. Sheikh Kholil Bangkalan is a national hero as well as a cleric who has earned the nickname of a professor of clerics and clerics who has deep thoughts on morals, fiqh, sharia, and muamalah education. The research method uses literacy studies by describing the thoughts of Sheikh Kholil Bangkalan. Data sources were obtained from journals, e-books, books, and websites. Data analysis in this study used content analysis. One of the findings from this study is that according to Syekh Kholil Bangkalan, the aim of education is to make students have noble morals, meaning that there is a change in the behavior of students in a better direction.